2011
DOI: 10.1007/s13402-011-0040-x
|View full text |Cite|
|
Sign up to set email alerts
|

High frequency microsatellite instability has a prognostic value in endometrial endometrioid adenocarcinoma, but only in FIGO stage 1 cases

Abstract: Abstract. Objectives:To analyze the prognostic value of microsatellite instability (MSI) in a population-based study of FIGO stage 1-4 endometrial endometrioid adenocarcinomas.Study design: Survival analysis in 273 patients of MSI status and clinico-pathologic features. Using a highly sensitive pentaplex polymerase chain reaction to establish MSI status, cases were divided into microsatellite stable (MSS), MSI-low (MSI-L, 1 marker positive) and MSI-high (MSI-H, 2-5 markers positive).Results: After 61 months me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…There have been reports indicating that MSI is a good prognostic factor in colorectal cancer and that MMR status does not contribute to prognosis in colorectal cancer [ 47 , 48 , 49 ]. There are many reports that there is no significant difference in survival rate between the MSI and MSS groups in endometrial cancer [ 50 , 51 , 52 , 53 ]. Taken together with the current results, the effect of MSI status on prognosis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports indicating that MSI is a good prognostic factor in colorectal cancer and that MMR status does not contribute to prognosis in colorectal cancer [ 47 , 48 , 49 ]. There are many reports that there is no significant difference in survival rate between the MSI and MSS groups in endometrial cancer [ 50 , 51 , 52 , 53 ]. Taken together with the current results, the effect of MSI status on prognosis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Although dMMR has been associated with a better prognosis in CRC, its prognostic significance in EC is unclear . Whereas many studies have reported worse survival and/or shorter disease‐free survival among patients dMMR or microsatellite instability (MSI), other studies have demonstrated improved survival or no association . A recent meta‐analysis also demonstrated no association between MMR status and OS or RFS .…”
Section: Discussionmentioning
confidence: 99%
“…But in 2009, Bilbao, at al. reported that MSI is related to vascular invasion (p = 0.009) and advanced stage (p = 0.04) [8]. It is also noted that MSI has an independent predictive value for DFS and local DFS in early stage (p = 0.044), suggesting that MSI may have a predictive role in radiotherapy response in this group [6].…”
Section: Discussionmentioning
confidence: 82%
“…However, neither OS nor DFS was effected by MSI status in early stage (p = 0.284, p = 0.243). reported that MSI has prognostic value only for stage 1 cases in endometrioid adenocarcinoma (p = 0.005) [8].…”
Section: Discussionmentioning
confidence: 99%